Ultrafine Magnetic Particles: A DIET-Proxy in Organic Rich Sediments? - Ustra, Andrea Teixeira; Mendonça, Carlos; Leite, Aruã da Silva; Macouin, Melina; Doherty, Rory; Respaud, Marc; Tocuti, Giovana (Frontiers in Earth Science, 2021)
In this work we present results of the magnetic properties characterization of sediment samples from a brownfield site that is generating methane biogas in São Paulo–Brazil. We applied interpretation procedures (frequency dependent susceptibility and time-dependent Isothermal Remanent Magnetization) appropriate to study the ultrafine magnetic fraction response of the samples. The higher content of superparamagnetic (SP) particles correlates well with the detected biogas pockets, suggesting that the methanogens activity produces these ultrafine particles, different from the magnetic particles at other depth levels. We propose the use of two simple measurement and interpretation techniques to identify such magnetic particles fingerprints. The results presented here support the use of environmental magnetism techniques to investigate biogeochemical processes of anaerobic microbial activity.